DEVELOPMENT OF CIVIL LAW THROUGH EMPOWERING JURISPRUDENCE: A COMPARATIVE STUDY OF CIVIL LAW AND COMMON LAW SYSTEMS - Pinem, Faisal Hadi; Kamello, Tan; Purba, Hasim; Ikhsan, Edy (NOMOI Law Review, 2024)
The development of civil law in resolving disputes needs to be addressed by implementing court decisions that have permanent legal force in the form of jurisprudence. Civil law problems that are developing rapidly are unable to be followed by existing legal regulations, and are not even sufficient to answer all the problems in civil law itself. The research uses a normative juridical research type. Jurisprudence has a big role and contribution in the development of civil law to fill legal gaps and provide legal certainty. Article 10 Paragraph (1) Law no. 48 of 2009 states that "Courts are prohibited from refusing to examine, try and decide on a case submitted on the pretext that the law does not exist or is unclear, but is obliged to examine and try it". The position of jurisprudence in Indonesia, which adheres to a civil law system, adheres to the principle of freedom or is "persuasive precedent". Efforts to bring about legal convergence in certain cases are not possible. However, there are still legal similarities which can be used as a legal basis for resolving various problems in civil law in Indonesia. The role of the Supreme Court is very important in reviewing judges' decisions that are suitable for use as jurisprudence and carrying out an inventory of decisions in the field of civil law that constitute legal reform.